2007
DOI: 10.1158/1535-7163.mct-06-0686
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-stroma interactions in pancreatic ductal adenocarcinoma

Abstract: The host stromal response to an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
426
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(442 citation statements)
references
References 66 publications
6
426
1
6
Order By: Relevance
“…PDAC tumor stroma serves as a mechanical barrier and promotes tumor forma-tion, progression, invasion, and metastasis development. [32][33][34] Treatment with nab-paclitaxel alone or nab-paclitaxel in combination with gemcitabine has been shown to decrease cancer-associated fibroblast (CAF) content, inducing a marked alteration in cancer stroma that result in tumor softening both preclinically 29 and clinically 28 . In our studies, we also found that the G C nP doublet significantly reduced the number of a-SMA positive fibroblasts as well as reduced extracellular collagen.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC tumor stroma serves as a mechanical barrier and promotes tumor forma-tion, progression, invasion, and metastasis development. [32][33][34] Treatment with nab-paclitaxel alone or nab-paclitaxel in combination with gemcitabine has been shown to decrease cancer-associated fibroblast (CAF) content, inducing a marked alteration in cancer stroma that result in tumor softening both preclinically 29 and clinically 28 . In our studies, we also found that the G C nP doublet significantly reduced the number of a-SMA positive fibroblasts as well as reduced extracellular collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, spontaneous cross talk between epithelial and stromal cells induces the expression of genes in both the stroma and cancer cells. [63][64][65][66][67][68][69][70][71] These genes include classical cancer stroma markers that reportedly may promote oncogenic potential of adjacent epithelia. 2,3,[72][73][74] This is possibly due to the late presentation with carcinoma disease in human life span.…”
Section: Evolutionary Context For Cancer Promotion By Spontaneous Infmentioning
confidence: 99%
“…[115][116][117][118] The fibroblast response is hardwired in the genome as part of the cancer's resemblance to a chronic wound, aiming at support of epithelial cell survival and expansion. [119][120][121][122][123][124][125][126][127][128] In addition to parsimony, this hypothesis offers clear predictions to scientifically test against corresponding null hypotheses; (1) That co-culture of cancer cells with normal fibroblasts will induce expression of CAF-specific genes in the fibroblasts, [63][64][65][66][67][68][69][70][71] [63][64][65][66][67][68][69][70][71] Many of the genes shown to be activated in these co-cultures are known markers of CAFs in vivo, such as MMP1, MMP3, collagens, TNC, etc. Evidence that this reciprocal interaction promotes cancer includes the anti-cancer effect of Imatinib, on carcinoma animal models.…”
Section: The Reciprocal Interactions Model Of Cafsmentioning
confidence: 99%
“…Current chemotherapy of gemcitabine combined with EGFR tyrosine kinase inhibitor, Tarceva, provides a 4-month survival advantage at best. 15 Further, there is a lack of specific tumor markers for disease staging and early diagnosis. Hence, targeting the signaling pathway and the downstream players that can affect invasiveness and oncogenic aggressivity remains an exciting avenue to pursue therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Hence, there is evidence to warrant examination of downstream players of the pathway as potential targets for therapy. Nonetheless, H3 phosphorylation as a downstream event in the activation of the Ras-MAPK pathway in human pancreatic cancer cells has not been reported.…”
mentioning
confidence: 99%